2017
DOI: 10.1111/jce.13139
|View full text |Cite
|
Sign up to set email alerts
|

Fragmented QRS Is a Novel Risk Factor for Ventricular Arrhythmic Events After Receiving Cardiac Resynchronization Therapy in Nonischemic Cardiomyopathy

Abstract: In patients with nonischemic cardiomyopathy who received CRT, an fQRS-post was independently associated with SCD or ventricular arrhythmic events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…The presence of fQRS in HCM patients could predict a higher risk of all-cause mortality, a higher risk of cardiovascular disease mortality, and a higher risk of heart failure-related deaths. In a study performed by (Igarashi et al, [25], they found that fQRS was an independent risk factor for developing ventricular arrhythmias and sudden cardiac death in patients with non-ischemic cardiomyopathy treated with cardiac resynchronization. In a recently published study by (Attachaipanich and Krittayaphong,[26], they studied the value of fQRS in predicting in-hospital life-threatening arrhythmic complications in after STEMI.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of fQRS in HCM patients could predict a higher risk of all-cause mortality, a higher risk of cardiovascular disease mortality, and a higher risk of heart failure-related deaths. In a study performed by (Igarashi et al, [25], they found that fQRS was an independent risk factor for developing ventricular arrhythmias and sudden cardiac death in patients with non-ischemic cardiomyopathy treated with cardiac resynchronization. In a recently published study by (Attachaipanich and Krittayaphong,[26], they studied the value of fQRS in predicting in-hospital life-threatening arrhythmic complications in after STEMI.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with other techniques focused on the time or frequency domain, we consider that the wavelet transform may provide significant advantages. Although firstly reported, the analysis of QRS fragmentation on the time domain may be less useful than the analysis of the high-frequency content to detect patients at risk for SCD [ 2 , 8 , 9 ]. The main limitation of the analysis of fragmentation is that it is based on a subjective classification, with no absolute measurements, and thus it is more difficult to standardize.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, the physiological basis of fragmentation has been related to delays in conduction of the electrical wavefronts through the myocardium, mostly secondary to the interposition of scar and fibrotic tissue [ 4 , 5 ]. The latter mechanism also explain the late potentials usually recorded from the myocardium of patients with ischemic cardiomyopathy [ 6 , 7 ] and other clinical entities with a high risk of SCD such as Hypertrophic Cardiomyopathy [ 8 ] or Dilated Cardiomyopathy [ 9 ]. The Brugada Syndrome (BrS) [ 10 , 11 ] is a particular case in which functional mechanisms promoting delayed conduction explain the occurrence of delay/late potentials in the absence of fibrotic tissue [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although meaningful clinical usage of Tp-Te for prospective risk stratification for VA events and mortality in patients with cardiomyopathy has been demonstrated before, further risk stratification within three separate high-risk population with HF would be of clinical value [4]. Fragmented QRS (fQRS) is another risk predictor index on surface ECG for electro-mechanical dyssynchrony, VA, SCD and poor prognosis for patients with HF and hypertrophic cardiomyopathy [17], [18], [19], [20], [21], [22]. The purpose of this study was to assess If there is a distinction of various indices of TDR in three group of patients with HF (HFrEF- HfmrEF- HFpEF) and there is a relationship between fQRS and these indices in patients with HF.…”
Section: Introductionmentioning
confidence: 99%